Analisis Motivasi Kerja dalam Meningkatkan Kinerja Karyawan pada Eyelashbdl di Bandar Lampung - Shinta Septia; Vonny Tiara Narundana (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The purpose of this study is to analyze job motivation to improve the performance of Eyelashbdl's employees. The types of research used are descriptive and qualitative. The research was conducted at his Eyelashbdl using data sources obtained from interviews with the owner and two of her three informants. He uses a data-gathering technique in four stages: observation, interviewing, documenting, and providing information. As a result, it was found that work motivation plays an important role in supporting employee performance, and if employee performance is satisfactory, it can be said that Eyelashbdl employee performance is good, and the company's image can be improved. Factors that influence employee performance include providing annual bonuses, free lunches, meeting specific visit goals, working holiday bonuses, performance recognition, and the opportunity for free treatment at Eyelashbdl. Paying salaries annually can have a very positive impact on employee performance, reflected in the services they provide, and attracting customers through the convenience offered. However, the more employees you have, the faster your work will be, and the better your results will be. Eyelashbdl's Profit Growth Drives Employee Motivation.